The effectiveness of rural youth leadership: a case study in Kudat, Sabah - Romzi Ationg (Penerbit Universiti Malaysia Sabah, 2011)
If Sabah’s rural youth organisations are to be run effectively, they need strong leaders. This article discusses the issue of leadership and also examines the charge that these organisations are blighted by a lack of management. The data were collected through a self-administered questionnaire, the results of which were analysed using SPSS. In this study, one hundred youths with a mean age of 25 years were chosen as respondents. According to the results of the study, 89 percent of the respondents perceived there is no effective leadership in rural youth organisations in Sabah. The respondents also suggested that this problem can only be solved through intensive, one-to-one self-coaching of the leaders.